Is there a Case for Price-level Targeting? - Cournède, Boris (OECD Economics Department Working Papers, 2009)
There is a case, but there are also counter-arguments. With sufficient forward-looking behaviour among firms and households, price-level targeting can act as a powerful built-in stabiliser through automatic shifts in inflation expectations. This stabilisation mechanism reduces the need for large shifts in policy rates, alleviating the risk of hitting the zero lower bound of nominal interest rates and falling into a liquidity trap. Furthermore, credible price-level targeting can support capital accumulation by protecting the long-run purchasing power of money and reducing the inflation risk premium embedded in actual long-term real interest rates. However, price-level targeting can imply welfare-reducing policy-induced output volatility in situations where the degree of forward-looking behaviour is very low. The self-regulating capacity of price-level targeting can be undermined if central banks are not fully credible. Besides, aggressive inflation targeting can replicate some of (but not all) the benefits of price-level targeting. On balance, the case for adopting price-level targeting is not clear-cut, all the more so since transition costs are likely to be significant